2022
DOI: 10.1136/bmjopen-2021-058799
|View full text |Cite
|
Sign up to set email alerts
|

Patient preferences for atopic dermatitis medications in the UK, France and Spain: a discrete choice experiment

Abstract: ObjectivesWe aimed to quantify patient preferences for efficacy, safety and convenience features of atopic dermatitis (AD) treatments.Design and settingOnline discrete choice experiment survey.ParticipantsAdults in the UK, France and Spain who had used AD treatments during the past 2 years.Primary and secondary outcome measuresPreferences for attributes were analysed using a multinomial logit model. Willingness to make trade-offs was expressed as the maximum acceptable decrease (MAD) in the probability of achi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
2
4
0
Order By: Relevance
“…In line with the findings of the current DCE, Thomas et al ( 25 ) found that the mode of administration significantly impacted patients’ preferences. Participants in their study prioritized increased efficacy and reduced risk, but were willing to accept reduced efficacy to receive treatment orally every day instead of as injections every second week ( 25 ). In a qualitative study from 2022, Ervin et al ( 26 ) investigated the importance of treatment administration in patients with AD.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…In line with the findings of the current DCE, Thomas et al ( 25 ) found that the mode of administration significantly impacted patients’ preferences. Participants in their study prioritized increased efficacy and reduced risk, but were willing to accept reduced efficacy to receive treatment orally every day instead of as injections every second week ( 25 ). In a qualitative study from 2022, Ervin et al ( 26 ) investigated the importance of treatment administration in patients with AD.…”
Section: Discussionsupporting
confidence: 68%
“…In addition, attributes of time to onset of itch relief, probability of skin clearance at 16 weeks, and mode of administration were included in the DCE. The annual risk of malignancy was identified as the most important attribute across all attributes, highlighting the importance of safety in the view of the patients ( 7 , 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, patients expressed the preference for drugs with a rapid onset of action, oral administration, necessity of less frequent monitoring, and a flexibility in the administration schedule. They would trade in higher efficacy for these characteristics [72]. Similar results were obtained in a qualitative interview study in the UK and USA.…”
Section: Shared Patient-physician Decision-making In Adsupporting
confidence: 75%
“…Most patients are ready to accept adverse events for the efficacy of the treatment in general, as well as accepting the mode of administration [89]. A once-daily pill is usually chosen over an injection every 2 weeks as the preferred form of administration [92,95]. The prevalence of needle fear has been well documented in another survey highlighting that only 50% of respondents were willing to opt for an injectable treatment [90].…”
Section: Patients' Treatment Expectationsmentioning
confidence: 99%
“…The number of patients who prefer injections increases with age and is higher among those currently receiving biologics [88]. Patients prefer oral medications over topical treatments, often seeing the latter as "less convenient" and "time consuming to apply", which has a direct consequence on the adherence of the patients [89,95]. Nevertheless, some patients claim a fear of swallowing pills [89].…”
Section: Patients' Treatment Expectationsmentioning
confidence: 99%